2019
DOI: 10.1111/jcpe.13156
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of macrophage polarization in periodontal disease

Abstract: Aim To explore the M1/M2 status of macrophage polarization from healthy, gingivitis, and periodontitis patient samples. Materials and methods Gingival biopsies were collected from 42 individuals (14 gingivitis, 18 periodontitis, and 10 healthy samples) receiving periodontal therapy. Histomorphology analysis was performed with haematoxylin and eosin staining. Immunofluorescence was performed using a combination of CD68 (macrophages), iNOS (M1), and CD206 (M2) in order to acquire changes in macrophage polarizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 42 publications
3
93
0
Order By: Relevance
“…Here, we investigated the macrophages content within peri‐implantitis lesions and compared it with our previously reported cohort of periodontitis patients (Garaicoa‐Pazmino et al, ). Our results showed that soft tissues from periodontitis have an inflammatory infiltrate containing significant levels of CD68 + macrophages.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Here, we investigated the macrophages content within peri‐implantitis lesions and compared it with our previously reported cohort of periodontitis patients (Garaicoa‐Pazmino et al, ). Our results showed that soft tissues from periodontitis have an inflammatory infiltrate containing significant levels of CD68 + macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…Xue and colleagues used the transcriptional activation states of macrophage in M1 vs. M2 to identify nine distinct macrophage activation programs (Xue et al, ). Such findings could explain the double‐positive staining of macrophages with iNOS and CD206, which were noted in the present and previous study by our group (Garaicoa‐Pazmino et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations